ICT Curriculum Integration in the Context of the Learning Outcomes in Portugal - Costa, Fernando Albuquerque (2012)
The purpose of this paper is to discuss tangible and effective ways to integrate Information and Communication Technologies (ICT) into school curricula. In order to do so, we make use of severalyears of thoughtful consideration about this issue and, more specifically, of the work that we have recently developed in the context of the “Learning Outcomes” project hosted by the Portuguese Ministry of Education in 2010. The “Learning Outcomes” project is about developing tools and materials to help schools and teachers make informed choices concerning the national curriculum aims, and thus decide which learning experiences suit them the best. Advocating a decentralised curriculum development, these resources are to be used voluntarily and freely by schools as part of their pedagogical autonomy. One of the tools developed and already available is the set of learning outcomes for preschool, primary and middle school students (ages 3-14) covering all subject areas. Moreover, examples of teaching and evaluation strategies were provided for every subject area, so as to help teachers gain a better understanding of how the learning outcomes can be put into practice. In order to explain and share the work done regarding ICT, this paper presents and discusses the rationale that supported an ICT Learning Outcomes Framework based on four main competence domains: Information, Communication, Production and Security. After clarifying the concept of teaching and evaluation strategies used in the project, we discuss the implications these examples may have in teachers’ decisions about selecting content, pedagogy, resources and evaluation methods. This discussion seems even more necessary when it comes to ICT, as it is a domain which clearly benefits from open and flexible pedagogical processes that enforce a regular partnership between different subject areas. We believe that the underlying principles of the work presented here, as well as the products of such work, may contribute to a better understanding of the challenges schools and teachers face once they have decided that ICT use in teaching and learning is more than just a tool to serve different subject areas. It is undoubtedly an opportunity to implement strategies focusing on the cognitive and social development of learners. Nevertheless, we conclude that we need to continue to broaden and deepen our knowledge regarding the challenges and demands of this proposal because, in contrast to a mono-disciplinary approach, it means the school culture must change into a cooperative culture based on partnerships formed by everyone operating within school. This is, according to us, the way to successfully provide experiences that foster a complete and balanced development of the young people in today's society.